Fruitland: The Stanley Quaker Mission to the Kaw - Michael Stubbs (Symphony in the Flint Hills, 2012)
In 1833, as a boy of fifteen in the Quaker settlement of Salem, Ohio, Thomas Stanley was inspired to take up the missionary life based on discussions he overheard about a widely circulated letter, originally published in the March 1833 edition of the Chri
Keywords: Quaker; religion; Thomas Stanley; missionary; Christian Advocate and Journal; Salem; Ohio; Christian Wyandot; Native American; Indian; Nez Perce; Flathead; William Clark; Lewis and Clark; power; magical; nature; Big John Creek; Shawnee; Pearl Dixon; Merr